Estudio comparativo de los estilos parentales del Centro de cuidado diurno Cuna Más y el Centro de Estimulación Temprana Saberes - Chavez Segura, Olga Giovanna (2018)
This research has the purpose of determining the comparative study of the parental styles of the day care center called "CUNA MAS" and the early learning center for children called "SABERES". The sample of the research consisted of 21 parents, 19 women and 2 men, who were evaluated by a test of parenting styles of children. The results of the research test show that, the parents of the early learning center called "SABERES", show initiative for the upbringing of their children since they are democratic style parents, while in the day care center called "CUNA MAS "parents leave their children alone, in charge of babysitters, lack of emotions and there is no interest for achievements and upbringing, being parents of authoritarian style.